Brucellosis in livestock: First study on seroepidemiology, risk factors, and preventive strategies to manage the disease in Famenin, Iran - Maryam Adabi; Salman Khazaiee; Ali Sadeghi-Nasab; Saeed Alamian; Mohammad Reza Arabestani; Zahra Valiei; Jamal Gharekhani (Veterinary World, 2022)
Background and Aim: Brucellosis is an infectious disease in humans and livestock. The disease is endemic in many regions of Iran, for example, Hamedan Province. Knowledge of infection rate and associated risk factors is essential to control and prevent the disease. The study aimed to estimate the prevalence of brucellosis and associated risk factors in cattle, sheep, and goats in Famenin, Hamedan Province, West of Iran.